2016
DOI: 10.2214/ajr.16.16168
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Single-Kidney Function and Volume in Living Kidney Donors Using Dynamic Contrast-Enhanced MRI

Abstract: DCE-MRI-derived values for single-kidney function and volume in kidney donors were significantly higher than those in control subjects and suggest a future potential benefit of DCE-MRI for diagnostic and prognostic structural and functional assessments in living kidney donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…Correlation between eGFR based on creatinine clearance and GFR measured using DCE MRI was significant when fat‐registered images were used, although agreement was limited (ICC of 0.38). This is worse compared to results reported recently by Eikefjord et al , who found an ICC of 0.49 in living kidney donors. In nephrectomized subjects, Tipirneni‐Sajja et al found comparable results for DCE MR‐based GFR measurement.…”
Section: Discussioncontrasting
confidence: 91%
“…Correlation between eGFR based on creatinine clearance and GFR measured using DCE MRI was significant when fat‐registered images were used, although agreement was limited (ICC of 0.38). This is worse compared to results reported recently by Eikefjord et al , who found an ICC of 0.49 in living kidney donors. In nephrectomized subjects, Tipirneni‐Sajja et al found comparable results for DCE MR‐based GFR measurement.…”
Section: Discussioncontrasting
confidence: 91%
“…It is possible that individual variations in sympathetic tone might have attenuated the effect of testosterone on kidney volume. Testosterone has been shown to counteract sympathetic tone of the afferent renal arteriole (Lu et al ., ), which in turn increases renal blood flow and consequently, influences renal volume (Eikefjord et al ., ). It is also possible that the study did not have sufficient statistical power due to the small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…Living kidney donation is considered the ultimate treatment for renal diseases. The link between the GFR derived from DCE‐MRI and iohexol GFR highlights the diagnostic value of DCE‐MRI for kidney donors . Using DCE‐MRI, Eikefjord et al showed that donors with a single remaining kidney have higher blood flow, higher GFR, and larger renal parenchymal volume .…”
Section: Applications Of Renal Fmrimentioning
confidence: 99%